Blood pressure in minorities screened for the Multiple Risk Factor Intervention Trial (MRFIT). - Sherwin, R (1996)
THE AUTHORS PRESENT DATA FROM 361, 662 MEN ages 35 to 57, screened from 1973 to 1976 for possible participation in the Multiple Risk Factor Intervention Trial (MRFIT). Volunteers identified themselves as "white," "black," "Oriental," "Spanish American," "American Indian," or "other." They also noted if they were taking medication for diabetes. A trained technician measured blood pressure after participants had rested for 5 minutes, using the fifth Korotkoff sound to define diastolic pressure and averaging the second and third of three readings. Differences among the groups included the following: blacks had consistently higher systolic and diastolic blood pressure (SBP and DBP) than other groups; Orientals had slightly lower pressure than other nonblack groups; American Indians had somewhat higher pressure than other nonblack groups at ages 35 to 44 but lower at ages 45 to 54; Hispanics in Miami and Davis, California, had significantly higher SBP and DBP than whites in the same area; Orientals in California had significantly higher DBP (but not SBP) than whites in California.